Diagnosing Conceptual Fragmentation in Black Sea Security: A Bibliometric Mapping Approach (2021–2026) - Haris, Umiyati; Paryati, Andi Niniek (Jurnal Administrasi Karya Dharma, 2026)
This study finds the Black Sea not only as an arena of geopolitical competition, but also as a space where knowledge is produced in a fragmented way. The region has often been discussed as a site of rivalry between Russia and NATO, yet existing studies remain scattered across different topics and have not been integrated into a clear analytical framework. Therefore, this research seeks to address this gap by mapping research patterns to identify where these separations occur. Using bibliometric analysis with a co-occurrence technique (2021–2026), out of 755 terms, 32 met the minimum threshold (≥4), and 19 were selected as the final units of analysis. The identified conceptual clusters include war policy, the Russia–Ukraine conflict, territorial annexation, NATO’s role in the security architecture, Türkiye’s position as a regional actor, and the dynamics of Russian elites (Putin/Kremlin). The findings show that these clusters are not strongly interconnected, indicating that the research remains fragmented. In addition, the Russia–Ukraine conflict emerges as the most dominant topic, resulting in uneven academic attention across other issues. This study argues that the Black Sea should be understood not only as a strategic arena, but also as a fragmented epistemic space. It encourages a more reflexive approach and highlights the importance of connecting different strands of research to achieve a more comprehensive understanding of this complex region.